1967
DOI: 10.1111/j.1365-2818.1967.tb04513.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the relation between structure and fluorescence of azo dyes

Abstract: SYNOPSIS Though azo dyes are not fluorescent in solutions, many azo dyes become fluorescent when bound to tissues. This fluorescence is determined largely by the aromatic components of the dye molecules. Like chromophores, these fluorophores are affected by other groupings in dye molecules. Relatively short, compact systems of conjugated double bonds or linking of such resonators by insulating groups favours fluorescence. Long chains of conjugated double bonds and coupling of azo groups in the 1,4‐ or 2,7‐ pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Puchtler et al (1967) first demonstrated that collagen could be distinguished using fluorescence microscopy and picro-sirius red staining, later using their technique to distinguish between collagen and elastin (Puchtler et al 1973;Rodgers et al 1967). Dolber and Spach (1987) introduced an improved method in which tissue sections are first treated with 0.2% phosphomolybidic acid (PMA) for 1-5 min, followed by the standard 90 min staining in 0.1% Sirius red F3BA in saturated aqueous picric acid.…”
Section: Transmural Collagen Concentration Distribution Determinationmentioning
confidence: 96%
“…Puchtler et al (1967) first demonstrated that collagen could be distinguished using fluorescence microscopy and picro-sirius red staining, later using their technique to distinguish between collagen and elastin (Puchtler et al 1973;Rodgers et al 1967). Dolber and Spach (1987) introduced an improved method in which tissue sections are first treated with 0.2% phosphomolybidic acid (PMA) for 1-5 min, followed by the standard 90 min staining in 0.1% Sirius red F3BA in saturated aqueous picric acid.…”
Section: Transmural Collagen Concentration Distribution Determinationmentioning
confidence: 96%
“…[5] Moreover, there are marked difference observed in fluorescence between solution-phase and solid immobilized azo dyes. [7] While promising for the desired application, challenges of storage and delivery exist with aryl diazonium ions, often requiring in situ generation. Our recent work masking aryl diazonium ions as triazabutadienes led us to investigate their usage as a convenient source of this fluorophore-generating moiety.…”
mentioning
confidence: 99%
“…It may be surprising that the fluorescence of azo and bisazo compounds has received relatively little attention in cytochemistry and cell biology, possibly due to some misleading statements claiming that introduction of an azo group abolishes the emission (for a detailed discussion see Puchtler et al 1967;Raap 1986). However, fluorescence properties of several azo and bisazo dyes are well known to textile chemists (Puchtler et al 1967(Puchtler et al , 1983, and they have some applications in cell and tissue staining reactions (Davis and Sauter 1977;Van der Kooy and Kuypers 1979;Harrison et al 1981;Puchtler et al 1983;. Recently, it has been reported that the colored azo-naphthol products of the diazonium salts fast red TR and fast violet LB (formed in situ for the demonstration of alkaline phosphatase activity) showed red fluorescence (Murdoch et al 1990;Ziomek et al 1990;Kamalia et al 1992;Speel et al 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it has been reported that the colored azo-naphthol products of the diazonium salts fast red TR and fast violet LB (formed in situ for the demonstration of alkaline phosphatase activity) showed red fluorescence (Murdoch et al 1990;Ziomek et al 1990;Kamalia et al 1992;Speel et al 1992). Some attempts have been made to correlate the chemical structure of dyes with fluorescence properties (Puchtler et al 1967;Berlman 1971;Juarranz et al 1986). The extent of a resonant chromophoric system can be assessed by means of the CBN, which describes the overall π-conjugation of the molecule (Horobin 1980(Horobin , 1982.…”
Section: Discussionmentioning
confidence: 98%